Quality of sleep among hypertensive patients in a semi-urban Nigerian community: a prospective study - Alebiosu, Olutayo C; Ogunsemi, Olawale O; Familoni, Oluranti B; Adebayo, P B; Ayodele, O E (Postgraduate medicine, 2009)
Sleep complaints are common in patients with chronic medical disorders; however, the prevalence of "poor sleep" in patients with chronic hypertension is not yet known in Nigeria. In the general population, insomnia negatively impacts quality of life. The objective of this study was to examine the quality of sleep among Nigerian hypertensive patients. The study aimed to measure the prevalence of "poor sleep" in hypertensive patients and to examine the association between quality of sleep and the severity of hypertension in this population. Quality of sleep was measured using the Pittsburgh Sleep Quality Index (PSQI) in chronic hypertensive patients attending a tertiary hospital in Nigeria. This was compared with normal control subjects. The mean age of the hypertensive patients was 58.15 +/- 9.65 years (range, 19 - 76 years). This did not differ from the controls at 58.7 +/- 10.8 years. A total of 80 (60.6%) respondents were females with a mean age of 58.3 +/- 12.2 years while 52 (39.4%) were males with a mean age of 58.8 +/- 11.7 years. The mean body mass index (BMI) was 26.42 +/- 4.13 kg/m2 (range, 18.9 - 36.4 kg/m2), with 63.1% of the respondents being either overweight or obese. The mean systolic blood pressure was 167.4 +/- 21.8 mm Hg (range, 100 - 210 mm Hg) while the mean diastolic blood pressure was 96.7 +/- 14.9 mm Hg (range, 60 - 130 mm Hg). Fifty-six (42.4%) hypertensive subjects were "poor sleepers" (global PSQI > 5), with a global mean PSQI of 5.03 +/- 3.28. This was significantly more than 17.3% of control subjects, with a mean global PSQI of 3.10 +/- 0.83. Among the hypertensives, there was no statistically significant relationship between the global PSQI and the age (P = 0.653), sex (P = 0.710), BMI (P = 0.253), systolic (P = 0.145), and diastolic blood pressure (P = 0.827). Poor sleep is common in hypertensive patients and may be associated with lower health-related quality of life. Large-scale, prospective, longitudinal studies on quality of sleep in hypertensive patients are needed to confirm the high prevalence of impaired quality of sleep in this population and to examine the association between severity of hypertension and quality of sleep while controlling for potential confounding variables. We hypothesize that severity of hypertension directly influences quality of sleep, and poor quality of sleep may worsen hypertensive conditions.